2022
DOI: 10.4315/jfp-21-410
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sources of Salmonella Lymph Node Infection in Special-Fed Veal Calves

Abstract: Peripheral lymph nodes have been implicated as potential contaminants of ground beef, yet the source and timing of Salmonella lymph node (LN) infection in cattle is still unclear, limiting targeted intervention. Thus, the aim of this study was to leverage the vertical integration of special-fed veal production to identify preharvest environmental exposures, namely livestock trailers or harvest facility holding pens where calves spend 30 min. to 4 hrs, that result in Salmonella LN infection. Ten cohorts of 80-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Briefly, survey materials (e.g., cover letter, consent statement, questionnaire, postcard to decline participation, prepaid return envelope) were mailed to all formula‐fed veal calf producers within two U.S. production companies ( n = 32 producers in Company 1; n = 70 producers in Company 2) in February and December 2019, respectively. Most of the formula‐fed veal industry in the United States is highly integrated, and companies rely on contract growers to raise calves for veal production (Locke et al, 2022). There are a small number of formula‐fed veal production companies in the United States, and therefore, the two production companies in this study represent a substantial portion of the total production.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, survey materials (e.g., cover letter, consent statement, questionnaire, postcard to decline participation, prepaid return envelope) were mailed to all formula‐fed veal calf producers within two U.S. production companies ( n = 32 producers in Company 1; n = 70 producers in Company 2) in February and December 2019, respectively. Most of the formula‐fed veal industry in the United States is highly integrated, and companies rely on contract growers to raise calves for veal production (Locke et al, 2022). There are a small number of formula‐fed veal production companies in the United States, and therefore, the two production companies in this study represent a substantial portion of the total production.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial culture and salmonella isolation were performed as previously described using standard operating procedures reviewed and accredited by the American Association of Veterinary Laboratory Diagnosticians. 9 The salmonella isolate underwent antimicrobial susceptibility testing (AST) using the broth microdilution technique using the bovine BOPO7F Sensititre plate (Thermo Fisher Scientific), as described by the manufacturer. Minimum inhibitory concentrations were categorised based on Clinical Laboratory Standards Institute (CLSI breakpoints) where available.…”
Section: Case Presentationmentioning
confidence: 99%
“…Research in this area is crucial as preventing asymptomatic Salmonella infections in cattle has been ineffective. Increasing evidence has shown that lymph nodes are a significant source of ground beef Salmonella contamination [8][9][10]. However, despite intensive research, little is known about how the pathogen reaches and survives within the lymph nodes of healthy animals.…”
Section: Introductionmentioning
confidence: 99%